C3-Symmetric cinchonine-squaramide as a recyclable efficient organocatalyst for tandem Michael addition–cyclisation of malononitrile and nitrovinylphenols. Issue 14 (15th August 2016) - Lv, Wenxing; Guo, Chao; Dong, Ze; Tang, Shi; Liu, Bin; Dong, Chune
Graphical abstract: Abstract: The tandem enantioselective Michael addition/cyclisation reaction of malononitrile and nitrovinylphenols was catalysed by a recoverable C 3 -symmetric cinchonine-squaramide organocatalyst 1a to afford the 2-amino-4 H -chromene-3-carbonitrile derivatives in excellent yields (up to 95%) and with excellent enantioselectivities (up to 98% ee) under mild reaction conditions. Furthermore, this catalyst can be easily recovered four times without loss in activity or enantioselectivity.